Performance Challenges for Female Teachers: Dissecting Workload and Dual Role Conflict - Chauhan, Rahul; Nurhamidah, Umi; Pariyanti, Eka; Sulastri, Susi; desastra, Yolla zelika (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
The purpose of this research is to understand how workload and dual role conflict affect the performance of married female teachers in junior high schools in East Lampung. Data were collected through questionnaires and interviews. The research was conducted in junior high schools in East Lampung, with 138 respondents as samples from the same population. Samples were taken using a non-probability method with saturated census sampling. Data analysis used multiple linear regression run through SPSS v23 software for Windows. The research results indicate that: (1) Workload has a negative and significant effect on the performance of female teachers. (2) Dual Role Conflict also has a negative and significant effect on the performance of female teachers. (3) Together, workload and dual role conflict have a significant effect on the performance of female teachers.